Assessment For Sustainable Tourism Development In Hoi An City Using The Model Of Hilary Du Cros - TRUONG, Thi Xuan Dao; PHAM, Huong Trang; TRAN, Duc Thanh; Sukana, I Made (JURNAL DESTINASI PARIWISATA, 2021)
Considering the potential resources related to human factors, cultural heritage to develop tourism is the desire of tourism managers. The study used the Hilary du Cros method to evaluate the tourism value of the World Cultural Heritage: Hoi An Ancient Town. There are two surveyed sample groups: the first group is The Tourism Management Group with N1 = 88 and the second group is The Tourist Group with N2 = 220 to determine the points to evaluate the appeal market and robusticity in tourism exploitation at the destination of Hoi An Ancient Town. The evaluation results show that the World Cultural Heritage of Hoi An Ancient Town has a strong market attraction, high cultural value, and sustainable development, located in cell M (1.3) in the appeal matrix and cultural values/ sustainable development of Hilary du Cros. Keyword: Tourism evaluation, Robusticity and market appeal matrix, Hilary du Cros model, Hoi An Ancient Town.